Gas Chromatography analysis of a c1-c5 hydrocarbon column - Madon, Rais Hanizam; Fawzi, Mas; Osman, Shahrul Azmir; Alimin, Ahmad Jais; Razali, Mohd Azahari; Sarwani, Muhamad Khairul Ilman; Abeden, Zulhelmy Zinil (UTHM, 2018)
A gas chromatography (GC) equipment was used to classify chemical elements in a sample through a separation method based on the relative molecular mass. This paper describes the replacement of a capillary C5 and above Hydrocarbon Column of a Perkin Elmer Clarus 500 GC with a capillary C1-C5 hydrocarbon column from a different manufacturer. The use of appropriate carrier gas and a new standard procedure for C1-C5 hydrocarbons column, which manage to yield the largest, short time appearance and most stable detector signal area’s patterns microVolt-seconds as qualitative and quantitative results were analysed. Several injector temperatures, sample split ratios, carrier gas flow rates and detector temperature were experimented. The effectiveness of nitrogen, helium and hydrogen as carrier gas were observed. The outcome showed that the combination of different column and GC equipment manufacturer works properly without any error. From the qualitative analysis of element configuration, the optimum setting found are; 250°C injector temperature, 1:15 split ratio, 2.5 ml / min flow rate and 275 ° C detector temperature. Hydrogen gas was found to be the best carrier for natural gas samples containing compounds that allot over a wide temperature range. In addition, a quantitative reference standard, the detector signal area microVolt-seconds against concentration of Methane gas was prepared to be used as a benchmark for C1-C5 hydrocarbon conversion reaction analysis.